The Visual Signs of Affluence in the Single Figurative Paintings of the Court Women in the Zand and Qajar eras and their Comparison with the Paintings of the Isfahan School - Ameneh Mafitabar (پیکره, 2021)
Problem Definition: Royal figurative painting, a style of Persian painting formed during the Zand era, continued until the end of the reign of the third Qajar Shah in Iran. This type of iconography received much recognition during the 37-year reign of Fath-Ali Shah and such artworks followed fixed rules. Given that visual symbols are further manifested comparatively, the main question of the study is as follows: How are the visual signs of affluence in the single royal figurative paintings of court women of the Zand and Qajar eras in comparison with the Iṣfahān school of painting?Objective: This study aimed to investigate the visual signs of affluence in the single royal figurative paintings of the Zand and Qajar eras restricted to the feminine custom.Research Method: In this analytical-comparative study, stratified random sampling was used to select artworks from twelve royal figurative paintings to be studied in comparison with four miniatures from Iṣfahān school.Results: Unlike the iconographies of women in Iṣfahān school, generally depicted in a reclined position in external spaces with simple and minimum backgrounds; during the Zand era and the first half of the Qajar era, women were painted in sitting, standing, dancing, and occasionally reclined positions in internal spaces with various kinds of foods, drinks and animals as signs of possessing wealth. In contrast with the preceding era, this pattern is not only defined in the style of painting but also in the view of opulence on the one hand and the female gender on the other.